Editorial: Positive youth development, mental health, and psychological well-being in diverse youth - Wiium, Nora; Ferrer-Wreder, Laura; Lansford, Jennifer E.; Jensen, Lene Arnett (Frontiers in Psychology, 2023)
An inverse association theoretically exists between indicators of thriving and adjustment problems. However, the unique characteristics of the contexts of diverse youth may present a more nuanced and complex connection between strengths and problems for some groups. Based on research from the Cross-National Project on Positive Youth Development (CN-PYD) and contributions from many other researchers from around the globe, the current Research Topic presents 30 articles that collectively examined the ways in which positive development intersects with indicators of mental health and well-being in over 45,000 children, adolescents, and emerging adults from diverse cultures and contexts in Africa, the Americas, Asia, and Europe. Published in different article formats, namely meta-analysis, study protocols, book reviews, and empirical papers, and applying varying research designs, such as cross-sectional, longitudinal, and intervention studies, the article collection presents shared and distinct findings that: 1) advance the understanding of positive development in diverse youth, 2) provide new insights into the connection between strengths and problems as well as 3) inform intervention science. The ecological and strengths-based perspectives of the article collection, the multiplicity in methodology, as well as the inclusion of culturally diverse youth and international collaboration of researchers, all come together to contribute to a more holistic view of youth development and help to further an increasingly valid developmental science. In advancing the field of PYD, in terms of research, policy, and practice, both challenges and advantages that come with diversity in methods, contexts, theories, and expertise, along with the inclusion of youth voices and choices need to be addressed.